2011
DOI: 10.4236/me.2011.23027
|View full text |Cite
|
Sign up to set email alerts
|

International Linkages of the Indian Commodity Futures Markets

Abstract: This paper investigates the cross market linkages of Indian commodity futures for nine commodities with futures markets outside India. These commodities range from highly tradable commodities to less tradable agricultural commodities. We analyze the cross market linkages in terms of return and volatility spillovers. The nine commodities consist of two agricultural commodities: Soybean, and Corn, three metals: Aluminum, Copper and Zinc, two precious metals: Gold and Silver, and two energy commodities: Crude oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…They find a positive and significant correlation between volatility and trading volume for all commodities, no significant relationship between volatility and open interest, and an asymmetric relationship between trading volume and open interest. Kumar and Pandey (2011) examined the cross market linkages of Indian commodity futures with futures markets outside India. However, all these studies focus on the price volatility of commodity futures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They find a positive and significant correlation between volatility and trading volume for all commodities, no significant relationship between volatility and open interest, and an asymmetric relationship between trading volume and open interest. Kumar and Pandey (2011) examined the cross market linkages of Indian commodity futures with futures markets outside India. However, all these studies focus on the price volatility of commodity futures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature survey has shown that particular attention has been paid to: commodity futures markets (e.g., among developed markets: Yang et al (2003); among developing markets: Kumar and Pandey (2011)) and stock index futures (e.g., among developed markets: Yang and Bessler (2004); among developing markets: Ahmad and Rahim (2009)). …”
Section: Literature Reviewmentioning
confidence: 99%
“…As summarized by Kumar and Pandey (2011), the majority of research findings on linkages across different countries' commodity futures markets suggest that there are stronger international market linkages in highly traded commodities compared to relatively less traded commodities, also that a dominant role is played in price discovery process by developed markets.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the few studies is Kumar and Pandey (2011), which analyzes the cross-market volatility linkages and spillover effects between Indian and U.S. gold futures. One of the few studies is Kumar and Pandey (2011), which analyzes the cross-market volatility linkages and spillover effects between Indian and U.S. gold futures.…”
Section: Literature Reviewmentioning
confidence: 99%